Developing Deutsch Im Hotel Teaching Media with Canva Media - Insenalia sampe roly Hutagalung; S. Lamriana Hutagalung (Jurnal Ilmu Sosial dan Humaniora, 2026)
Learning a foreign language, especially German, requires innovative, interactive, and contextual teaching media to improve students' motivation and understanding. One important topic in German language learning in the tourism sector is Deutsch im Hotel (German in Hotels), because communication competencies in the hospitality sector are highly needed by graduates who will work in the tourism and hospitality industry. The urgency of this research lies in the limited availability of interesting, easily accessible, and appropriate teaching media for students, resulting in the learning process often being monotonous and ineffective. The objectives of this research are (1) to develop interactive and contextual Canva-based Deutsch im Hotel teaching media, (2) to test the feasibility of the teaching media through validation by material experts and media experts, and (3) to assess the effectiveness of the teaching media in improving students' vocabulary understanding and communication skills in hotel service situations. Through the use of Canva, teaching media is expected to be more visual, creative, and easy to use by both lecturers and students in online and offline learning. The targeted outputs of this research include: (1) Canva-based Deutsch im Hotel teaching media products that are ready to be used in lectures, (2) scientific articles published in accredited national journals, (3) reports on the results of media feasibility tests that can be used as references for the development of similar media, and (4) improving the quality of German language learning through creative digital media. Thus, this research is expected to be able to provide a real contribution to innovation in foreign language learning in higher education and support the improvement of student competencies in facing the needs of the global tourism industry